STUDI FENOMENOLOGI: INTERAKSI KEKUASAAN DENGAN KOMPROMI SEBAGAI PEMICU FRAUD PENGADAAN BARANG DAN JASA PADA IMPLEMENTASI E-PROCUREMENT DI PEMERINTAH KABUPATEN POWERERI - Ginting, Rafles (ABDI EQUATOR, 2021)
The purpose of this research is to understand stakeholder responses and e-procurement practices related to fraud potential and practice of e-procurement implementation in POWERERI province government. The response was assessed by various observations and experiences put forward by stakeholders in government. This research was conducted by qualitative method, case study approach, which was done on the government of POWERERI province. The informants interviewed consisted of the Inspectorate Officer, BPK, BPKP, ULP, the Partners and Members of the DPR of POWERERI Province. The results of this study indicate a different response from various stakeholders who expressed their opinion about the role of e-procurement as prevention of fraud as the response that arises varies greatly from being able to adapt to the defensive attitude, from passive to active, from unconscious to control, powerless to change and from habit to utilization that can be done best, depending on the conditions experienced by the stakeholders against the implementation of e-procurement in the government of POWERERI Province. Based on the view there are five types of response strategies, but different in terms of attribution to the condition of this study, which shows only three types of responses. The existing responses are due, acquisition, avoid, and compromies. In addition to the indications of fraud in the practice of e-procurement in the provincial government of POWERERI spearheaded by the interaction of power and compromise, where these two things are very related and interlocked. In relation used the relevant theory that linked the theory of Institutional Logic.